Optimal contracts under competition when uncertainty from adverse selection and moral hazard are present - Natalie Packham (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
In a continuous-time setting where a risk-averse agent controls the drift of an output process driven by a Brownian motion, optimal contracts are linear in the terminal output; this result is well-known in a setting with moral hazard and under stronger assumptions adverse selection. We show that this result continues to hold when in addition reser- vation utilities are type-dependent. This type of problem occurs in the study of optimal compensation problems involving competing principals.
Keywords: C00; 330; Principal-agent modelling; contract design; stochastic process; stochastic control